Avian Papilloma and Squamous Cell Carcinoma: a Histopathological, Immunohistochemical and Virological study. (February 2020) - Jones, A.L.; Suárez-Bonnet, A.; Mitchell, J.A.; Ramirez, G.A.; Stidworthy, M.F.; Priestnall, S.L.
Summary: In this retrospective study, we describe the histopathological findings in seven papillomas and 45 squamous cell carcinomas (SCCs) from psittacine birds, raptors and domestic fowl. The age of affected birds ranged from 3 to 40 years, with median age significantly higher in psittacines ( P = 0.014). The majority of tumours were located in the skin (24/52, 46.2%) or uropygial gland (10/52, 19.2%). Thirty of the SCCs (66.7%) were well differentiated and 15 (33.3%) were poorly-differentiated. SCCs exhibited a significantly higher degree of nuclear pleomorphism ( P = 0.005) and a greater proportion were ulcerated ( P = 0.001) compared with papillomas; however, there was no significant difference in mitotic count (MC) or inflammation score. The expression of cyclo-oxygenase (COX)-2 and E-cadherin was investigated by immunohistochemistry. The COX-2 total score (TS) was significantly higher in SCCs compared with papillomas ( P = 0.002), but the difference between COX-2 TS of well- and poorly-differentiated SCCs was not significant. COX-2 labelling was predominantly cytoplasmic, but some tumours had concurrent membranous and/or perinuclear labelling. SCCs with membranous labelling had a significantly higher MC ( P = 0.028). A significantly higher proportion of SCCs were negative for E-cadherin compared with papillomas ( P = 0.042), but there was no significant difference between well- and poorly-differentiated SCCs. Fourteen papillomas and SCCs from psittacines were also tested by polymerase chain reaction for the presence of Psittacus erithacus papillomavirus 1 and Psittacid herpesvirus 1, but all samples tested negative. We demonstrate for the first time the expression of COX-2 and E-cadherin in avian tissues, and suggest that these markers may be useful in differentiating papillomas from SCCs, particularly when sample size is small.